Effects of dietary salt levels on monocytic cells and immune responses in healthy human subjects: a longitudinal study - Yi, Buqing; Titze, Jens; Rykova, Marina; Feuerecker, Matthias; Vassilieva, Galina; Nichiporuk, Igor; Schelling, Gustav; Morukov, Boris; Choukèr, Alexander (Translational research : the journal of laboratory and clinical medicine, 2015)
Increasing evidence indicated that excess salt consumption can impose risks on human health and a reduction in daily salt intake from the current average of approximately 12 g/d to 5–6 g/d was suggested by public health authorities. The studies on mice have revealed that sodium chloride plays a role in the modulation of the immune system and a high-salt diet can promote tissue inflammation and autoimmune disease. However, translational evidence of dietary salt on human immunity is scarce. We used an experimental approach of fixing salt intake of healthy human subjects at 12, 9, and 6 g/d for months and examined the relationship between salt-intake levels and changes in the immune system. Blood samples were taken from the end point of each salt intake period. Immune phenotype changes were monitored through peripheral leukocyte phenotype analysis. We assessed immune function changes through the characterization of cytokine profiles in response to mitogen stimulation. The results showed that subjects on the high-salt diet of 12 g/d displayed a significantly higher number of immune cell monocytes compared with the same subjects on a lower-salt diet, and correlation test revealed a strong positive association between salt-intake levels and monocyte numbers. The decrease in salt intake was accompanied by reduced production of proinflammatory cytokines interleukin (IL)-6 and IL-23, along with enhanced producing ability of anti-inflammatory cytokine IL-10. These results suggest that in healthy humans high-salt diet has a potential to bring about excessive immune response, which can be damaging to immune homeostasis, and a reduction in habitual dietary salt intake may induce potentially beneficial immune alterations.